Conception of a synthesis pozzolan from sediment dams calcined (Case: Gargar dams) - Ouhba K.; Benamara L.; Hadj Hamoui A.; Hamwi A.; Loye Pilot Marie - D. (MATEC Web of Conferences, 2014)
Silting of dams is undoubtedly the most dramatic consequence of the erosion problem in Algeria. In spite of the great ways implemented for the construction of retaining structures, the storage of water remains confronted with the difficulties of their management. It is as important to be invested to prevent silting as to build a new dam. There are two levels of Investigations: that is to say to prevent the solid matters from arriving in reserve. There, it is a question of putting obstacles to break the forces strength of surface waters but one can expect only partial results. The second solution is the evacuation of the sediments by a suitable management of the basic matters and desilting by dredging which requires the use of an external energy. But considering the great quantity of the sediments of silting, we sought to make profitable the vases recovered with an aim of dumping down the costs associated with desilting. The research work undertaken herein concern the case of Gargar dam, as a real case of silted dams in Algeria and whose rate of silting is important. The significant amounts of rejected silts present environmental problems and their use as local raw materials for the manufacturing of materials in civil engineering contributes to its resolution. The results of the physical and mineralogical characteristics of the sediments of Gargar dam directed us towards the design of a synthetic pozzolan. For, we carried out calcination of the silt at different temperatures up to 750 °C and prepared micro test samples of calcined silt-cement mixtures. The results show that the addition of 30% of sediments calcined at 750°C to cement permit to obtain a pozzolanic cement having similar characteristics with ordinary cement. This study shows therefore the possibility to value dam sediments as materials in the construction domain. The analysis by the diffraction of x-rays (X-ray) and the differential thermal analysis (DTA) show that the chemical reactions between principal minerals of the vase used and cement give the formation of new products such as the freezing of HSC and the tobermorite.